2015
DOI: 10.5433/1679-0359.2015v36n6supl2p4311
|View full text |Cite
|
Sign up to set email alerts
|

The effects of managerial systems on helminth infection in freerange chickens from northern Paraná, Brazil

Abstract: The effects of managerial systems on the occurrence of gastrointestinal helminths in Free-Range Chickens (FRCs) from northern Paraná, Brazil were investigated. The most predominant (23.3%; 61/262) cestode observed was Raillietina cesticillus; Heterakis gallinarum (71.4%; 187/262) and Ascaridia galli (45%; 118/262) were the predominant nematodes; Postharmostomum commutatum was the only trematode observed in 2.7% (7/262) of FRCs. The most elevated parasitic burdens were associated with Heterakis gallinarum, Asca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…This species is recognized as resulting in negative economic impact due to its ability to transport the microorganism responsible for histomonosis (Brandão-Simões et al, 2020;Cupo & Beckstead, 2019;Lozano et al, 2019;Tamara et al, 2019). The results obtained in the present study are in agreement with the results of Vieira et al (2015) in which 262 birds were evaluated (85.9% positive), most of which were infected with H. gallinarum (71.4% prevalence). The high prevalence, intensity and mean abundance of H. gallinarum may be closely related to its direct biological cycle, e.g., the continuous exposure of animals to helminth eggs distributed in the environment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This species is recognized as resulting in negative economic impact due to its ability to transport the microorganism responsible for histomonosis (Brandão-Simões et al, 2020;Cupo & Beckstead, 2019;Lozano et al, 2019;Tamara et al, 2019). The results obtained in the present study are in agreement with the results of Vieira et al (2015) in which 262 birds were evaluated (85.9% positive), most of which were infected with H. gallinarum (71.4% prevalence). The high prevalence, intensity and mean abundance of H. gallinarum may be closely related to its direct biological cycle, e.g., the continuous exposure of animals to helminth eggs distributed in the environment.…”
Section: Discussionsupporting
confidence: 91%
“…Several authors still seek to establish a correlation between the prevalence of helminths and some climatic variables, such as temperature, humidity and precipitation (Lozano et al, 2019). The climatic conditions of the city of Viçosa (average temperature 20.6 °C and 1229mm average annual rainfall) associated with the extensive breeding system, favorably influence the maintenance of direct biological cycle parasites, as well as the ubiquitous distribution of intermediate hosts of cestodes and trematodes (Permin et al, 1999;Ruff, 1999;Silva et al, 2018;Thapa et al, 2015;Vieira et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasites are common in intensive or organics systems of chickens, which is more conducive to the emergence of gastrointestinal parasites, favored by direct contact with soil and other organisms (RUFF, 1999;SHEIKH et al, 2015, VIEIRA et al, 2015. Helminths are responsible for economic losses due to decreased food intake, reduced growth and posture, leading to nutritional deficiencies that makes the birds susceptible to other infectious diseases and can lead to death (CARDOZO & YAMAMURA, 2004;UHUO et al, 2013;HASSAN et al, 2015;THAPA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Argentina, broiler chicken flocks were evaluated and 25% of flocks were shown infected but no correlation was found between nematodes and coccidian infections (De Franceschi et al, 2008). Previous studies in Brazil, have found broiler flocks infected by Ascaridia galli in 10/17 municipalities of São Paulo (Da Silva et al, 2018), in free-range flocks in the neighboring state (Paraná), with 45% infected (Vieira et al, 2015), and in Santa Catarina in 21.7% (Quadros et al, 2015). In our study, we show that raising broilers in Minas Gerais, previously shown to naturally occur A galli by Mendes et al (1976) and in our unpublished extension service, especially for longer and without preventive medication, may lead to highly significant infection.…”
Section: Resultsmentioning
confidence: 99%